PENDAMPINGAN PEMASARAN PRODUK MAKANAN BERBAHAN SINGKONG PADA UMKM DI DUSUN CANDI WETAN - Muhamad Aji Saputra; Achmad Nur Alfianto (khidmatan, 2021)
Most MSMEs in rural areas increase the value of local raw materials to produce a product. Utilization of local raw materials as superior products for SMEs is carried out in Magelang Regency such as in the Grabag District, especially in Ngasinan Village. One of the MSMEs that utilizes local raw materials is the center for making snacks made from cassava. The products are produced from these raw materials can also be quite numerous and varied. However, the amount of product produced has not been supported by good marketing. This is due to the lack of marketing personnel and the absence of a brand of the food product. Based on this, MSME needs to developed marketing strategies. In assisting marketing activities, providing any training on the use of social media as a marketing tool and creating product labels or brands are important and can become the identity of snack products made from cassava from Candi Wetan Village.